Variable anisotropic FOV for 3D radial imaging with spiral phyllotaxis (VASP). Issue 1 (27th August 2020) - Krishnamoorthy, Guruprasad; Smink, Jouke; Tourais, Joao; Breeuwer, Marcel; Kouwenhoven, Marc
Abstract : Purpose: To develop a new 3D radial trajectory based on the natural spiral phyllotaxis (SP), with variable anisotropic FOV. Theory & Methods: A 3D radial trajectory based on the SP with favorable interleaving properties for cardiac imaging has been proposed by Piccini et al ( Magn Reson Med . 2011;66:1049‐1056), which supports a FOV with a fixed anisotropy. However, a fixed anisotropy can be inefficient when sampling objects with different anisotropic dimensions. We extend Larson's 3D radial method to provide variable anisotropic FOV for spiral phyllotaxis (VASP). Simulations were performed to measure distance between successive projections, analyze point spread functions, and compare aliasing artifacts for both VASP and conventional SP. VASP was fully implemented on a whole‐body clinical MR scanner. Phantom and in vivo cardiac images were acquired at 1.5 tesla. Results: Simulations, phantom, and in vivo experiments confirmed that VASP can achieve variable anisotropic FOV while maintaining the favorable interleaving properties of SP. For an anisotropic FOV with 100:100:35 ratio, VASP required ~65% fewer radial projections than the conventional SP to satisfy Nyquist criteria. Alternatively, when the same number of radial projections were used as in conventional SP, VASP produced fewer aliasing artifacts for anisotropic objects within the excited imaging volumes. Conclusion: We have developed a new method (VASP), which enables variable anisotropic FOV for 3D radial trajectory with SP. For anisotropic objects within the excited imaging volumes, VASP can reduce scan times and/or reduce aliasing artifacts.